Unveiling the Method of Interpretation by Abdurrahman bin Nasir as-Sa’di in the Book ’Taisir al-Karim al-Rahman fi Tafsir Kalam al-Mannanâ€™ - Hamnah, Hamnah; Bakar, Achmad Abu; Firdaus, Firdaus (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This study aims to describe the methodology of interpretation utilized by Abdurrahman bin Nasir as-Sa’di in his book "Taisir al-Karim al-Rahman fi Tafsir Kalam al-Mannan." It seeks to identify the sources, methods, form, style, and interpretation techniques employed within the book. The research approach employed is library research, utilizing an exegetical approach. The primary data source for this study is the book "Taisir al-Karim al-Rahman fi Tafsir Kalam al-Mannan," with additional supporting data derived from books on ulum al-Qur’an and other interpretations. The data analysis method employed in this study is content analysis. The findings of this study reveal that Abdurrahman bin Nasir as-Sa’di’s methodology of interpretation in the Qur’an incorporates various ijmali methods. The forms of interpretation used are bi al-ma’sur (based on transmitted reports) and bi al-ra’yi (based on personal judgment) with a direct approach, while the style of interpretation is Adabi Ijtima’i (literary and collective). The sources of interpretation include the Qur’an, Hadith, statements of the companions, consensus of scholars, ulum al-Qur’an, and Arabic language. The interpretation encompasses textual, linguistic, systemic, logical, sociohistorical, teleological, and Sunni perspectives.